Doxycycline in the treatment of infections of the urinary tract: A review - Adel S. Al-Shukri; Mariya R. Kolomijceva; Sergei B. Petrov (ZAO "Consilium Medicum", 2024)
Research shows that microbial resistance to antibacterial drugs continues to increase, highlighting the need to find new strategies to combat infections. In this context, previously used antibacterial drugs such as doxycycline have begun to attract renewed attention from the medical community. In addition, recent studies are revealing new properties of this drug that may expand its role in clinical practice, opening up new prospects for use. The review describes the place of doxycycline in the treatment of sexually transmitted infections, presents treatment regimens for urethritis, pelvic inflammatory diseases, as well as the non-antimicrobial properties of the drug.